In vitro regeneration through axillary proliferation in carnation (dianthus caryophyllus l. Cv. Maldnes). - Abdul Aziz, Maheran; Winarto, B.; Abdul Rashid, Azmi; Ismail, Mohd Razi (2001)
In vitro regeneration through axillary proliferation was evaluated in carnation (Dianthusvcaryophyllus L. cv. Maldives) using shoot tip and nodal exp/ants placed on MS medium supplemented with 2.0 mgIL 6-benzyladenine (BA) and 0.9 mgIL a-naphthaleneacetic acid (NAA) (GR-I), 1.0 mg/L BA and 0.1 mgIL NAA (GR-2), 3.0 mg/L BA and 0.9 mg/L NAA (GR-3), and 0.5 mg/L zeatin (GR-4). Both the explants tested on the different concentrations and combinations of growth regulators showed high shoot production. Nodal explant and MS medium containing 1.0 mg/L BA and 0.1 mg/L NAA were the explant type and the appropriate growth regulator combination for axillary proliferation of D. caryophyllus L. c. v. Maldives. Vitrification of shoots was high and need to be solved.